Promoting the use of locally produced crops in making cereal-legume-based composite flours: an assessment of nutrient, antinutrient, mineral molar ratios, and aflatoxin content - Udomkun, Patchimaporn; Tirawattanawanich, C.; Ilukor, J.; Sridonpai, P.; Njukwe, E.; Nimbona, P.; Vanlauwe, Bernard (Elsevier, 2019)
Cassava, rice, and banana flours were used individually to replace wheat flour in cereal-legume-based composite flours. The proximate composition, mineral content, antinutritional effect, mineral molar ratios, and aflatoxin level were investigated. Replacing wheat flour with rice flour significantly (P < 0.05) improved protein, fat, potassium, and phosphorus content in samples. The molar ratios of phytate or oxalate to minerals (calcium and zinc) in all composite flours were lower than the reported critical values, except phytate to iron. However, all samples, except full replacement by rice flour, might not provide adequate zinc bioavailability when the effect of calcium and phytate on zinc absorption was collectively considered. Although all composite flours were contaminated with aflatoxins, only the control composed of wheat flour did not meet the EU regulatory threshold (4.0 µg/kg) for total aflatoxins. The findings showed that nutritional properties and aflatoxin content of composite flours can be improved by replacement with local crops.